The Image of the US—An Introduction to US-American Visual Cultures (KULT_online, 2011)
Christof Decker, media and cultural studies scholar at LMU Munich, presents with the collection Visuelle Kulturen der USA (Visual Cultures of the USA) the first German-language survey of US-American painting, photography, film, TV, and new media—and thereby a comprehensive and insightful introduction to the image worlds and self-images of the US. In this compendium, the history of technologies and cultural appropriations of visual cultures is treated in the same detailed manner as the development of themes, styles, and institutions which amount to the global "cultural meaning of visuality" (p. 9).